Perception of Preservice Elementary Teachers Regarding Teaching Vulnerable Population Groups - Yancovic Allen, Macarena Alejandra (2021)
Approximately 50% of Latin America´s youth pertains to a vulnerable population group. Specifically, at elementary schools in Chile, this percentage increases to 76.4%. Given this background, this study seeks to look at preservice school teacher perception regarding their classroom practice in lower-income settings. In this qualitative study, fourteen preservice teachers were interviewed, all majoring in Education at a private university in Chile. The actual interviews were then transcribed and classified according to the corresponding themes identified in the verbatim interview transcription. The results identify two main ideas related to the tension and challenges that preservice elementary school teachers perceived during their classroom field practice with students who pertain to vulnerable population groups. Each topic is divided into four subject headings: Working in a context of violence; teacher-student relationships; official school curricula versus the executed curriculum and, the sense of learned helplessness felt among students. The second subject area refers to the challenges teachers face and is classified according to the following headings: Interaction with students, promotion of values ​​in the classroom, managing emotions and finally, dealing with student frustration. The results of this study will, hopefully provide future teachers with a better skillset to be able to work in such challenging settings. It also serves as a precedent for teachers by improving their understanding of this phenomenon.